Early identification of HIV: empirical support for jail-based screening. - de Voux, Alex; Spaulding, Anne C; Beckwith, Curt; Avery, Ann; Williams, Chyvette; Messina, Lauren C; Ball, Sarah; Altice, Frederick L (PloS one, 2012)
Although routine HIV testing is recommended for jails, little empirical data exist describing newly diagnosed individuals in this setting.
Keywords: Adult; CD4 Lymphocyte Count; Cohort Studies; Cross-Sectional Studies; Female; HIV Infections; Humans; Male; Mass Screening; Middle Aged; Prisons; Young Adult